1997
DOI: 10.1902/jop.1997.68.9.857
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Expression of Gingival Fibroblasts Cultured on Membranes Used in Guided Tissue Regeneration

Abstract: Human gingival fibroblasts were cultured in vitro using as substrates an extracellular matrix (matrix) and polytetrafluoride (PTFE) membranes, which are used in guided tissue regeneration. To test the degree of biocompatibility of these membranes, the cellular proliferation and the accumulation of extracellular matrix (ECM) macromolecules were considered as parameters. The fibroblasts were cultured in vitro for 24 and 48 hours without serum on plastic, matrix, and PTFE membranes in the presence of 3H-thymidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 21 publications
9
53
2
7
Order By: Relevance
“…27 Similar findings have also been reported elsewhere. 28,29 The lack of tissue integration of e-PTFE might be due to the permanent denaturation of tissue protein after adsorption onto PTFE surfaces. 30 A denatured protein exposes epitopes that are normally hidden in the internal structure of the native protein, which may provide binding sites for other proteins or cells that could ultimately activate cellular cascades, leading to inflammation and a humeral response.…”
Section: Discussionmentioning
confidence: 99%
“…27 Similar findings have also been reported elsewhere. 28,29 The lack of tissue integration of e-PTFE might be due to the permanent denaturation of tissue protein after adsorption onto PTFE surfaces. 30 A denatured protein exposes epitopes that are normally hidden in the internal structure of the native protein, which may provide binding sites for other proteins or cells that could ultimately activate cellular cascades, leading to inflammation and a humeral response.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors obtained the same results, with limited attachment and proliferation of various cellular types on different guided bone regeneration membranes (Gabriel et al 1996;Payne et al 1996;Rothamel et al 2004;Takata et al 2001a;Wang et al 2002). Only Locci et al 1997 reported opposite findings. A small, but not statistically significant, viability decrease was observed on Inion after 13 weeks.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, HGFs were chosen in order to get results closer to normal phenotype behavior in comparison with immortal cell lines (Fukuda et al 2000;Hillmann et al 2002;Locci et al 1997;Payne et al 1996;Simain-Sato et al 1999). Optical microscopy of the bottoms of wells and SEM analysis of the Inion membranes lower face confirmed the absence of cells and a positive barrier effect until 13 weeks, while the manufacturer states an 8-12 weeks in vivo barrier effect.…”
Section: Discussionmentioning
confidence: 85%
“…Various types of collagen from different species, tissues, and organs have been used as barriers in animal and human studies (15). Low immunologic response, hemostasis promotion, chemotaxis stimulation for periodontal ligament and gingival fibroblasts, easy manipulation and ability to enhance tissue thickness in some situations are some of the advantages proposed for collagen membranes (15,16). Macrophages and polymorphonuclear leukocytes will resorb this material through enzymatic activity (17).…”
Section: Bioabsorbable Barrier Membranesmentioning
confidence: 99%